2017
DOI: 10.1155/2017/8319176
|View full text |Cite
|
Sign up to set email alerts
|

African Ancestry Gradient Is Associated with Lower Systemic F2‐Isoprostane Levels

Abstract: Context. Low levels of systemic F2-isoprostanes (F2-IsoP) increase the risk of diabetes and weight gain and were found in African Americans. Low F2-IsoPs could reflect an unfavorable metabolic characteristic, namely, slow mitochondrial metabolism in individuals with African ancestry. Objective. To examine differences in plasma F2-IsoPs in three groups with a priori different proportion of African ancestry: non-Hispanic Whites (NHWs), US-born African Americans (AAs), and West African immigrants (WAI). Design. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…Similarly, insulin-resistant obese patients exhibited high levels of urinary F 2 -IsoPs and oxidized low-density lipoprotein (LDL), when compared with normal-weight individuals [52]. Racial difference studies showed that Blacks exhibit lower F 2 -IsoPs than Whites in urine and plasma [53][54][55]. In contrast to ours, however, these studies were conducted in both males and females.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Similarly, insulin-resistant obese patients exhibited high levels of urinary F 2 -IsoPs and oxidized low-density lipoprotein (LDL), when compared with normal-weight individuals [52]. Racial difference studies showed that Blacks exhibit lower F 2 -IsoPs than Whites in urine and plasma [53][54][55]. In contrast to ours, however, these studies were conducted in both males and females.…”
Section: Discussioncontrasting
confidence: 58%
“…Numerous epidemiological cross-sectional and observational studies demonstrated a positive correlation between F 2 -IsoPs and obesity and increased risk of T2D [57,61,62]. However, conflicting reports show an inverse relationship, meaning that F 2 -IsoPs levels are decreased with weight gain in Blacks and Whites [50,53,54]. The reason for this inverse relationship has been postulated to be due to a compensatory mechanism in obese patients and that negative energy balance (weight loss) leads to a decrease in energy expenditure, while positive energy balance (weight gain) leads to an increase in energy expenditure [63].…”
Section: Discussionmentioning
confidence: 99%
“…A small (27 healthy, smoking medical students) study that had no non-smoking controls; another study that compared circulating levels of 8-iso-PGF 2a in smokers and non-smokers (242 ± 147 and 103 ± 19 pmol/L, respectively) with levels falling to 156 ± 67 pmol/L after 2 weeks of smoking cessation (Morrow et al 1995) and a very small study (heavy smokers n ¼ 5; moderate smokers n ¼ 5; non-smokers n ¼ 14) that showed 8-iso-PGF 2a levels falling within 3 weeks of cessation but failing to reach levels seen in non-smokers (Reilly et al 1996). Normal plasma levels of 8-iso-PGF 2a are affected by ethnic background with one study showing that West African immigrants had lower 8-iso-PGF 2a levels than US-born African Americans who themselves had lower levels than non-Hispanic white Americans (Annor et al 2017). Similar differences have been reported for urinary levels of 8-iso-PGF 2a (Il'yasova et al 2012) Thromboxane B2 TXB2A potentially important platelet-derived marker is thromboxane A2 (TXA2).…”
Section: -mentioning
confidence: 99%
“…Consistent with this observation, ancestry differences in smoking-related metabolites and carcinogens have been reported ( Pérez-Stable et al, 1998 ; Benowitz et al, 2011 ; Khariwala et al, 2014 ; Jain, 2015 ), and different levels of these compounds may underlie the observed differences by ancestry in genetic interactions upon smoking exposure. Additionally, there is some evidence for greater systemic oxidative stress ( Il’yasova et al, 2012 ; Morris et al, 2012 ; Annor et al, 2017 ; Kim et al, 2020 ) and inflammation ( Albert et al, 2004 ; Khera et al, 2005 ; Akinyemiju et al, 2019 ; Zahodne et al, 2019 ) among Americans of African vs. European ancestry. Exposure to cigarette smoke, a rich source of oxidants, on a background of elevated oxidative stress and inflammation may provoke a greater response among these individuals, manifesting as an interaction with smoking that differs by ancestry.…”
Section: Discussionmentioning
confidence: 99%